COVID-19 Smart Diagnosis in the Emergency Department: all-in in Practice. Issue 3 (4th March 2022) - Mouliou, Dimitra S.; Pantazopoulos, Ioannis; Gourgoulianis, Konstantinos I.
ABSTRACT: Introduction: Coronavirus Disease 19 (COVID-19) diagnosis has been a major problem in most Emergency Departments (EDs) and other senior care facilities. Various clinical manifestations, and the several radiologic and laboratory data combined with the misleading test results to identify the virus, are responsible for certain misdiagnoses, especially in suspected cases needing urgent management and treatment. Although emergency and other front-line physicians struggle to manage COVID-19 patients, still existent cases with ambiguous diagnosis trammel the ED safety and responsibility. Areas Covered: This review article summarizes on a large scale the common information for the medical history, clinical examinations, radiology and laboratory data for SARS-CoV-2. We summarize the available literature using the PubMed, Science Direct and EMBASE databases published until December 2021 on the general information for COVID-19 diagnosis, and, finally, we propose algorithms for a precise and on-the-spot diagnosis the disease. Expert Opinion: COVID-19 diagnosis has appeared to be such ambiguous, and physicians need to correlate medical history, medical examination, potential extrapulmonary manifestations, along with laboratory and radiologic data, for a prompt COVID-19 diagnosis.